2011
DOI: 10.9734/bjmmr/2011/382
|View full text |Cite
|
Sign up to set email alerts
|

The Entrapment of Paclitaxel in PLGA Nanoparticles Increases its Cytotoxicity against Multiresistant Cell Line

Abstract: Paclitaxel (Ptx) is a taxane anticancer mitotic inhibitor, widely used in oncology for the last 20 years. Poor solubility of Ptx, as a consequence using of toxic solvents such as Cremofor EL, high affinity to P-glycoprotein are associated with serious side effects due to hypersensitivity reactions, low bioavailability and low therapeutic index. Development of new delivery solvent-free forms of Ptx is one of the key research problems in modern cancer chemotherapy. Ptx loaded into polylactic-co-glycolic acid (PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…An EE higher than 85% was observed for formulations with 50 to 90 μg of PTX, while for 100 µg, the loss of PTX was high, decreasing the EE to 74% ( Table 1 ). These results agree with previously reported data by Bojat et al, who found that PTX:PLGA ratios below 1:100 ensured a low drug loss [ 21 ]. Based on our results, it can be concluded that the formulation obtained using 80 μg of PTX may be considered as optimal for the development of the chemo-photothermal therapy system.…”
Section: Resultssupporting
confidence: 93%
“…An EE higher than 85% was observed for formulations with 50 to 90 μg of PTX, while for 100 µg, the loss of PTX was high, decreasing the EE to 74% ( Table 1 ). These results agree with previously reported data by Bojat et al, who found that PTX:PLGA ratios below 1:100 ensured a low drug loss [ 21 ]. Based on our results, it can be concluded that the formulation obtained using 80 μg of PTX may be considered as optimal for the development of the chemo-photothermal therapy system.…”
Section: Resultssupporting
confidence: 93%
“…This strong improvement was hypothesized to be due to a significant internalization of these nano-objects in both glioma cells compared to the free formulation. 38 However, in the F98 cell line, the effect was even more spectacular, with a PF of 50 for PLGA and 100 for PLGA/P188 Teva V R -loaded NPs. An increase in the cytotoxicity of encapsulated etoposide has already been reported by others, 17 but to our knowledge, this was the first time that such a huge difference was observed.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Among biodegradable and biocompatible nanoparticles, poly(lactic-co-glycolic acid) (PLGA) nanoparticles, which are designed to target cancer cells, have been proven to improve the pharmacological and therapeutic properties of drugs and extensively used for drug delivery. [12][13][14][15][16][17][18][19][20][21] Among these studies, Herceptin (HER; Trastuzumab) was used as targeting ligand on PLGA nanoparticles for breast cancer targeting. 13,19,21 HER is approved as an antibody for the treatment of human epidermal growth factor receptor type 2 (HER2)-positive metastatic breast cancers, and the receptor is overexpressed in 25-30% of the invasive breast cancers.…”
Section: Introductionmentioning
confidence: 99%